MicroRNAs as biomarkers for breast cancer - Canatan, Duran; Sönmez, Yonca; Yılmaz, Özlem; Çim, Abdullah; Coşkun, Hasan Şenol; Sezgin Göksu, Sema; Ucar , Selda; Aktekin, Mehmet Rıfkı (Acta Biomedica Atenei Parmensis, 2021)
Breast cancer is the most common type of cancer among women and the most frequent cause of death due to cancer among women. The lack of standard biomarkers in the early diagnosis of breast cancer, microRNAs (miRNA) have been of interest recently. Although, miRNAs are 19-24 nucleotide-long non-coding RNA species, they have crucial roles in many areas from organogenesis to carcinogenesis. This study has been conducted to investigate miR 21, miR 27b, miR 125a, miR 155, miR 200c, miR 335 miR373 as biomarkers in the early diagnosis of breast cancer; a selection based on the literature. Two miRNAs, miR 181 and miR 192 were selected as the endogenous control. MiRNAs were obtained from 5 cc blood samples taken from 20 breast cancer patients and 20 healthy people. 10 microRNAs were studied using Real Time PCR method. As a result, the quantities of miR 21, miR155 and miR125 ​​were significantly higher in the breast cancer group than in healthy controls. We suggest that performing validation studies in wider populations can help the use of miRNAs as biomarkers in the early diagnosis of breast cancer.